Manajemen Display Produk dan Stock Opname sebagai Strategi Peningkatan Efisiensi pada Batik Fajar Indah Solo - Putri, Laras Dwi Linggarani; Ellyana, Nabila Sastika; Setiawan, Fery (Yayasan Arrahman Nahdlatul Wathan, 2024)
This research discusses the implementation of product display and stock taking management strategies as an effort to increase operational efficiency in the retail environment. The main focus is on the role of interns in applying product naming concepts to make things easier for customers and on the stock taking process carried out by employees during store closures. The research results show that effective product display management can shorten customer shopping time and increase their independence, while stock taking is key in maintaining store inventory accuracy. These findings contribute to the practical understanding of how management strategies can be implemented to improve customer experience and operational efficiency in the retail industry.